Evaluating Specivity, Sensitivity, Positive and Negative Predictive Values of CA125 for Diagnosing Ovarian Cancer - Elahe Fini; Neda Nasirian; Bahram Hosein Beigy (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2021)
Background and Aim: Ovarian cancer is among the most common cancers in women worldwide. CA125 is the most frequent biomarker used in the screening for ovarian cancer. CA125 has no high sensitivity and specificity as a screening test in the medical community; however, because of being simple and noninvasive, it is almost always requested for evaluation and ruling out cancer. It plays an important role in the treatment and post-treatment process, the prediction of prognosis, and the relapse of the disease. The present study aimed to determine the relationship between a high level of CA125 tumor marker and ovarian cancer by detecting spesivity, sensivity, positive and negative predictive values. Methods & Materials: In this cross-sectional study, all cases undergoing CA125 test in Velayat Hospital in 2017-1028 were evaluated for having ovarian cancer. In addition, the CA125 level was compared between healthy individuals and patients with ovarian cancer. Finally, the obtained data were analyzed using SPSS. Ethical Considerations: The present study was approved by the Qazvin University of Medical Sciences (Ethics Code: IR.QUMS.REC.1396.316). Results: In this study, 35.3% of the study participants received a definite diagnosis of ovarian cancer. Generally, CA125 values were negative in 41.8% and positive in.58.2% of the study subjects. The sensitivity of the test was measured as 80.1%, the specivity as 53.6%, the positive predictive value equaled 48.4%, and the negative predictive value was measured as 83%. There was a significant relationship between age and the presence of ovarian cancer, and serum CA125 levels. Conclusion: The present study suggested that age and the serum level of CA125 were statistically significant. Finally, CA125 levels were significantly related to ovarian cancer. It provided moderate specivity and specivity as well as low positive predictive value and high negative predictive value as a tumor marker; it is valuable for ruling out of tumor but not appropriate as a screening test.